Development of support material for health professionals who are implementing Shared Decision-making in breast cancer screening: validation using the Delphi technique. Issue 2 (1st February 2022) - Hernández-Leal, María José; Codern-Bové, Núria; Pérez-Lacasta, María José; Cardona, Angels; Vidal-Lancis, Carmen; Carles-Lavila, Misericòrdia
Abstract : Background: The Literature is no report support material on Shared Decision-making applied to breast cancer screening that is intended for Spanish health professionals. The researcher created both a handbook and a guide for this topic using an adaption of the Three-talk model. Objective: A Delphi method will be used to reach an agreement among experts on the contents and design of a manual and guide, designed by the research team, and to be used by health professionals in the application of SDM in breast cancer screening. Design: A qualitative study. The content and design of the handbook and the guide was discussed by 20 experts. The Delphi techniques was in an online mode between July and October 2020 and researchers used Google forms in three rounds with open and closed questions. The criterion established for consensus was a coefficient of concordance (Cc) above 75, for questions using a Likert scale of 1–6—in which 1 meant 'completely disagree' and 6 'completely agree'—with a cut-off point equal to or higher than 4. Results: Participants considered the Three-talk model suitable for the screening context. The handbook sections and level of detail were considered satisfactory (Cc=90). The summary provided by the clinical practice guide was considered necessary (Cc=75), as it was the self-assessment tool for professionals (Cc=85). Content was added: addressing the limitations of the SDM model; extending the number of sample dialogues for health professionals; providing supplementary resources on using Patient Decisions aids and adding references on communication skills. Conclusions and applications: The first handbook and clinical practice guide providing unique SDM support material for health professionals have been developed. The handbook and guide are useful and innovative as supporting material for health professionals, but training strategies for SDM and a piloting plan for the use of materials are requested, in order to facilitate its implementation.